Industrial Light & Magic : the art of innovation - Glintenkamp, Pamela (New York : Abrams, 2011)
'Industrial Light & Magic tells the story, through the words of filmmakers, artists, and technicians, of the visual effects house, Industrial Light & Magic, which was founded by George Lucas in 1975'--
Includes bibliographical references and index.
Keywords: Industrial Light and Magic (Studio); Cinematography -- Special effects; Cinematographers -- United States -- Interviews